The role of national minorities in the state and national revival of Bulgaria (1877–1914) - Klejn, Zbigniew (Balcanica Posnaniensia. Acta et studia, 2001)
The article analyzes the significance of national minorities in the process of rebuilding Bulgarian statehood and shaping the modern Bulgarian nation after liberation from Ottoman rule. The author aims to determine the place of Turks, Greeks, Jews, Armenians, Gypsies, and other communities in Bulgarian life between 1877 and 1914. The study applies a historical method based on statistical data, official materials, and relevant scholarly literature. The research shows that despite the considerable emigration of the Turkish population after the Russo-Turkish War, Bulgaria retained its multiethnic character. Various groups participated in the country’s economic and social life, although their position was often constrained by the dominant concept of the nation, identified with Orthodoxy and the Bulgarian language. The author discusses demographic changes among minority populations and their significance for the development of the state. The conclusions indicate that Bulgaria’s national revival was shaped not only by ethnic Bulgarians but also by numerous minority communities that played an important role in the country’s economic and social life.